Mercury-free synthesis of pincer [C^N^C]AuIII complexes by an oxidative addition/CH activation cascade - Eppel, Daniel; Rudolph, Matthias; Rominger, Frank; Hashmi, A. Stephen K. (ChemSusChem, 2020)
Starting from the commercially available dimethyl sulfide‐gold(I) chloride complex (DMSAuCl) and diazonium salts in the presence of 2,6‐di‐tert‐butyl‐4‐methylpyridine as base, symmetric and unsymmetric [C^N^C]AuIIICl complexes were synthesized in a selective, photosensitizer‐free, photochemical reaction using blue LED light. This new protocol provides the first mercury‐free synthesis of these types of pincer‐complexes in moderate‐to‐excellent yields, starting from a readily available gold(I) precursor.